LEGAL IMPLICATIONS OF REGIONAL HEAD ELECTIONS WITH A SOLE CANDIDATE: A PERSPECTIVE OF STATE ADMINISTRATIVE LAW - Arifin, Firdaus (Cepalo, 2024)
The phenomenon of sole-candidate regional head elections in Indonesia has posed several challenges to democratic principles, particularly with regard to legitimacy, accountability, and public participation. This research aims to analyze the legal implications of regional head elections with sole candidates from the perspective of Administrative Law and evaluate their impact on democracy. The method used in this study is normative legal research, employing a legal and conceptual approach that includes a detailed analysis of election regulations, legal doctrines, and relevant literature studies. This method provides a robust framework for understanding the interplay between regulatory frameworks and democratic principles. The research findings indicate that elections with a sole candidate have the potential to undermine the legitimacy of the elected leader, reduce political accountability, and decrease voter participation rates. As a result, there is an urgent need to reform the electoral regulatory framework in Indonesia. Key recommendations include lowering the nomination threshold to foster competition, increasing transparency in the nomination process to ensure fairness, and strengthening political education to encourage public participation. These steps aim to enhance the quality of democracy and prevent the recurrence of sole-candidate elections in the future.